2014
DOI: 10.4103/2277-9175.148249
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, and performance of medical staff of teaching healthcare settings about hepatitis B and C in Isfahan, Iran

Abstract: Background:hospital personnel are at high risk of exposure, infection, and transmission of viral hepatitis. The present study aimed at investigating the knowledge, attitude, and performance of health service providers to provide them with the information required for their educational promotion on viral hepatitis.Materials and Methods:This cross-sectional study was conducted on 400 staff of the forenamed healthcare settings such as on nurses, midwives, licensed practical nurses, and lab officials in Isfahan, I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…However, this level of immunization coverage is not sufficient to protect HCWs against occupationally acquired hepatitis B virus infections. This finding is in agreement with the results from another study that reported that proper hepatitis B vaccination was carried out by 81.4% of HCWs in Isfahan, Iran (26). The hepatitis B vaccination status in HCWs who are at an increased risk of exposure to bloodborne infections have also been found to be suboptimal.…”
Section: Discussionsupporting
confidence: 83%
“…However, this level of immunization coverage is not sufficient to protect HCWs against occupationally acquired hepatitis B virus infections. This finding is in agreement with the results from another study that reported that proper hepatitis B vaccination was carried out by 81.4% of HCWs in Isfahan, Iran (26). The hepatitis B vaccination status in HCWs who are at an increased risk of exposure to bloodborne infections have also been found to be suboptimal.…”
Section: Discussionsupporting
confidence: 83%
“…These results indicate that there is a need for more HBV health promotion, targeted education, and training of nurses and midwives. Other studies reported that the level of the knowledge of hepatitis is low among different populations, including HCW, in several areas worldwide [2325].…”
Section: Discussionmentioning
confidence: 99%
“…Level of HBV knowledge among physicians, 17,20,21 nurses, 22,23 students, 24,25 hepatitis B-infected patients 26,27 and non-infected individuals in society 5,28 was reported in the past. However, to our knowledge, this is the first study that was carried out by a CP and includes intervention and evaluation of the intervention's effectiveness after a certain amount of time.…”
Section: Discussionmentioning
confidence: 99%